Diversity of Soil Fauna and Its Role to Decomposition Rate of Hevea barsilliensis Litter at Kebun Percobaan Cibodas – Ciampea Bogor - Noor Farikhah Haneda; Widia Asti (Jurnal Silvikultur Tropika, 2014)
Indonesia is one of the tropical countries that has a rich biodiversity. Forest is natural habitat for soil fauna to maintain the continuity of their life. However, there is limited information about soil fauna, particularlly in Indonesia, therefore it needs to do the research about identification of soil fauna and its roles towards the process that occurs in the soil. This research was conducted at Kebun Percobaan Cibodas - Ciampea Bogor and Forest Entomology Laboratory of the Faculty of Forestry IPB. The steps undertaken in this study were identify of soil fauna and analysed decomposition rate. Results showed that soil fauna found in research sites for 12 weeks observation period consists of: a phylum (Arthropoda), three classes (Hexapoda, Arachnida and Chilopoda), 18 orders (Acari, Blattaria, Coleoptera, Collembolla, Diplura, Diptera, Dermaptera, Geophilomorpha, Hymenoptera, Isoptera, Lithobiomorpha, Opiliones, Psocoptera, Siphonaptera, Scolopendromorpha, Scorpionida, Solifugae, dan Thysanoptera), 34 families and 42 genus. Based on plot location, average litter decomposition rate per two-week were 35.07% (edge), 33.02% (middle), and 32.07% (interior). The highest decomposition rate occurred in early weeks of decomposition time which happen on the second week. Relationship between total soil fauna biodiversity with decomposition rate is straight line. The corelation between rate of litter decomposition with litter weight towards decomposition time is strongly negative (Pearson correlation = - 0.846). Plot location and harvesting time significantly affected towards weight litter decrease and rate of decomposition.